Abundancia, tamaño y estructura poblacional del tiburón punta blanca de arrecife, Triaenodon obesus (Carcharhiniformes: Carcharhinidae), en Bahía Chatham, Parque Nacional Isla del Coco, Costa Rica - Zanella, Ilena (2012)
Approximately 12 species of shark inhabit at Coco Island National Park (PNIC); some are migratory, such as the hammerhead shark (Sphyrna lewini) and whale shark (Rincodon typus), and others are resident, like the whitetip shark (Triaenodon obesus). The whitetip shark is a species related to coral reefs, it inhabits coastal environments and is nocturnal and, it is very common in tropical waters, but there are few studies worldwide. In fact, only short researches have been done about their behavior at PNIC. Therefore, this study aimed to give data about the abundance, size and population structure of the whitetip shark at Chatham Bay in Coco Island National Park, providing baseline information for monitoring its population which is also very vulnerable to climate change. In order to accomplish this aim, a mark-recapture method was used, as well as underwater visual counts to determine their relative abundance and visual recaptures at Chatham Bay. The most effective hours for tagging were between 18:00 and 22:00 (sunset), when the whitetip sharks were more active probably related to foraging behavior. In addition, the depth was a relevant factor for tagging, sharks were caught in shallow water (10.9±1.9m). This species prefers to feed in shallow water and this behavior is probably related to the distribution and occurrence of rock and coral reefs in Chatham Bay. Based on the results, whitetip shark do not have a defined spatial ontogenic segregation, since in the same sites both juveniles and adults were found. The study confirmed that whitetip shark use specific residence sites: during the tagging trips, different individuals were recaptured; and during the underwater counts, at least 32.76% of tagged sharks were observed. The average length of the tagged sharks was 101.8±12.1cm (130.0cm maximum and 71.0cm minimum). The relative abundance of the whitetip shark in Chatham Bay observed was estimated on 49.5±10.4 sharks/hour. Furthermore, using the recapture data obtained during the night tagging expeditions, a population of 408 (IC = 181-1050) sharks was estimated.